The Effects of Nordic Walking With Poles With an Integrated Resistance Shock Absorber on Cognitive Abilities and Cardiopulmonary Efficiency in Postmenopausal Women - Domaszewska, Katarzyna; Koper, Magdalena; Wochna, Krystian; Czerniak, Urszula; Marciniak, Katarzyna; Wilski, Maciej; Bukowska, Dorota (Frontiers in Aging Neuroscience, 2020)
Late adulthood is associated with atrophy of brain areas, which contribute to cognitive deterioration and increase the risk of depression. On the other hand, aerobic exercise can improve learning and memory function, ameliorate mood, and prevent neurodegenerative changes. This study demonstrates the effect of Nordic walking (NW) and Nordic walking with poles with an integrated resistance shock absorber (NW with RSA) on the BDNF and GDNF serum levels and determines correlations with cognitive functions and depression symptoms as well as aerobic capacity and body composition in postmenopausal women. These relationships with the use of NW with RSA as a new form of exercise have not been described thus far. In this study, 31 women (NW - 16, NW with RSA - 15) participated in eight weeks of training. The findings showed that only NW with RSA training caused a significant decrease in body mass and body mass index (p < 0.05). There were no significant changes in GDNF levels between groups studied. Regarding BDNF, a significant decrease (p < 0.05) in the NW group and an increase (not statistically significant) in the NW with RSA group was found. A comparative analysis of cognitive and depression outcomes and changes in BDNF and GDNF concentration showed no significant differences in the efficacy of either form of training. Training loads resulted in a significant increase in VO2max in both the NW (p < 0.01) and NW with RSA (p < 0.05) groups. This indicates an improvement in cardiopulmonary efficiency of the examined women.